“One Health” Approach for Health Innovation and Active Aging in Campania (Italy) - De Luca, Vincenzo; Tramontano, Giovanni; Riccio, Luigi; Trama, Ugo; Buono, Pietro; Losasso, Mario; Bracale, Umberto Marcello; Annuzzi, Giovanni; Zampetti, Rosa; Cacciatore, Francesco; Vallefuoco, Giannamaria; Lombardi, Alberto; et al. (Frontiers in Public Health, 2021)
This article describes how innovations are exploited in Campania (Italy) to improve health outcomes, quality of life, and sustainability of social and healthcare services. Campania's strategy for digitalization of health and care and for healthy aging is based on a person-centered, life-course, “One Health” approach, where demographic change is considered capable of stimulating a growth dynamic linked to the opportunities of combining the “Silver Economy” with local assets and the specific health needs of the population. The end-users (citizens, patients, and professionals) contribute to the co-creation of products and services, being involved in the identification of unmet needs and test-bed activity. The Campania Reference Site of the European Innovation Partnership on Active and Healthy Aging is a flexible regional ecosystem to address the challenge of an aging population with a life-course approach. The good practices, developed in the context of research and innovation projects and innovative procurements by local stakeholders and collaborations with international networks, have been allowing the transfer of innovative solutions, knowledge, and skills to the stakeholders of such a multi-sectoral ecosystem for health.